DETERMINAN KEPUASAN NASABAH TABUNGAN RAMADHAN BERKAH DI BPRS ATTAQWA KARAWACI TANGERANG - Nurul Alim, Muhammad; Muchtar, Evan Hamzah; Maulida, Umi Aisyah (STAI Asy-Syukriyyah, 2024)
This study aims to analyze the effect of service quality and product quality on customer satisfaction of the Ramadhan Berkah Savings at BPRS Attaqwa Karawaci. The research method used is quantitative with a multiple linear regression approach, involving a sample of 51 respondents. Data was collected through questionnaires and analyzed using SPSS 21. The results show that service quality significantly affects customer satisfaction with a significance value less than 0.05, while product quality also has a significant effect with a significance value approaching 0.05. Simultaneously, both service quality and product quality significantly affect customer satisfaction. This study suggests that BPRS Attaqwa should continue to improve service and product quality to enhance customer satisfaction.